Current approaches and potential challenges in the delivery of gene editing cargos into hematopoietic stem and progenitor cells - Murugesan, Ramya; Karuppusamy, Karthik V.; Marepally, Srujan; Thangavel, Saravanabhavan (Frontiers in Genome Editing, 2023)
Advancements in gene delivery and editing have expanded the applications of autologous hematopoietic stem and progenitor cells (HSPCs) for the treatment of monogenic and acquired diseases. The gene-editing toolbox is growing, and the ability to achieve gene editing with mRNA or protein delivered intracellularly by vehicles such as electroporation and nanoparticles has highlighted the potential of gene editing in HSPCs. Ongoing phase I/II clinical trials with gene-edited HSPCs for -hemoglobinopathies provide hope for treating monogenic diseases. The development of safe and efficient gene-editing reagents and their delivery into hard-to-transfect HSPCs have been critical drivers in the rapid translation of HSPC gene editing into clinical studies. This review article summarizes the available payloads and delivery vehicles for gene editing HSPCs and their potential impact on therapeutic applications.